TRAINING ON MAKING HAND SOAP AS AN ALTERNATIVE INCOME DURING THE COVID-19 PANDEMIC IN KARANG TARUNA YOUTH IN MAYANGAN VILLAGE : PELATIHAN PEMBUATAN HAND SOAP SEBAGAI ALTERNATIF PENDAPATAN DI MASA PANDEMI COVID-19 PADA PEMUDA KARANG TARUNA DESA MAYANGAN - Diah Dinaloni; Henky Muktiadji; Ahmad Saikhu Wahid (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2022)
The Covid-19 pandemic isn't over yet. Soap is an alternative to maintain health. The purpose of this PKM is to provide training on making hand soap as an alternative income during the Covid-19 pandemic for youth youth in Mayangan Village. The method of implementing PKM is divided into: (1) The preparation stage which is divided into socialization and introducing the tools and materials used; (2) The implementation stage which is divided into a training stage with practical methods and interactive dialogue. The results of the training produced 100 bottles of hand soap, it is assumed that the net profit for each bottle is Rp. 4,860. Hand soap in the form of liquid soap on the market can be sold at a price of IDR 6,000 to IDR 7,000, so it is assumed that the profit that can be obtained per bottle is IDR 2,000 and intensive assistance so that participants can make hand soap independentlyand (3) the evaluation stage, in which the PKM evaluations are: (1) The support and participation of the participants greatly supports the success of the activity; (2) The presentation of materials, demonstrations at the training made many participants understand in detail all the materials and practices being taught, so that PKM is said to be running smoothly according to the plans and targets